Perancangan Sistem Informasi Akademik Pada Sekolah Menengah Kejuruan Negeri (SMKN) 1 Lintau Buo Menggunakan PHP MYSQL - Eko Amri Jaya; Veni Wedyawati (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2018)
The school website is a vehicle for schools to show themselves to the global community, as well as a medium of information for anyone who wants to know more about the school. The school website gets attention, good responses from various parties from education staff, students and the community. State Vocational High School 1 Lintau Buo (SMK N 1 Litau Buo) is one of the National Vocational High School Vocational Schools (SMK SSN) in Tanah Datar District which needs to interact and socialize with the wider community by providing complete and clear information about the school. Previously this school has never had an Academic Information System as a media campaign, and provision of information to students, parents, guardians and the wider community. Therefore, the school still uses manual way in conveying information. Manual way in delivering such information is felt to still have many shortcomings, such as the coverage of pemebaranya still less extensive and limited information content. The results of this study are: An Academic Information System built with PHP and MySQL can work with the ability: can perform input and storage process faster, smaller data files, due to using mysql database, and can be operated easily.